The Contributions of Teacher's Pedagogical Habitual to the Quality of Learning Services for Children with Special Needs in Inclusive Elementary Schools - Sunarsih, Diah; Nurbaeti, Rizki Umi (Journal of Primary Education, 2018)
Inclusion education at Elementary School is a solution for providing education services for children with special needs who cannot access education at the Extraordinary School so that children with special needs are academically served. Organizing learning in inclusive schools cannot be separated from the role of the teacher. This study aims to determine the contribution of teacher pedagogical habitual to the quality of learning services for children with special needs in inclusive elementary schools in Brebes Regency. The focus of this research is teacher pedagogical habitual towards the implementation of quality learning services for children with special needs in the implementation of inclusive schools in elementary schools. The sample is 35 children. The analysis test used is a Regression test. The results of the F test indicate that the significance value is 0.000. The significant value < 0.05, so it can be concluded that there is a contribution of teacher's pedagogical habitual to the quality of learning services for children with special needs in inclusive schools in Brebes Regency and shows the direction of positive contributions. R square value obtained in the calculation is 0.531. This means that pedagogical habits have an effect of 53% on the quality of inclusion learning services, and 47% are influenced by other factors not examined in this study. The results of the F test indicate that the significance value is 0.000. The significant value < 0.05, so it can be concluded that there is a contribution of teacher's pedagogical habitual to the quality of learning services for children with special needs in inclusive schools in Brebes Regency and shows the direction of positive contributions.